To be or Renminbi: Trend in the Evolution of the International Monetary System - Malovic, Marko G (Industrija, 2014)
By joining the recent research bandwagon in international finance, this paper reexamines the potential of Chinese yuan for becoming a leading world currency. After analysing historical perspective and the ongoing state of affairs in de facto tripolar global monetary system, both external and internal impediments to internationalisation of the ‘redback’ are given a due consideration. In light of portfolio rebalancing urges in developing countries’ FX reserves structure, as well as China’s own interest, a role for SDR, bitcoin, gold and alike substitutes comes under investigation too. Notwithstanding the fact that Triffin’s dilemma makes a spectacular comeback as equally perplexing mirror-image in regard to options available for currencies aspiring to usurp the US dollar on the world’s reserve denominator throne, if global recession and financial crisis remnants fail to recede any time soon, yuan can become one of the leading international currencies within only a decade or so.